Tissue architecture delineates field cancerization in BRAFV600E-induced tumor development - Schoultz, Elin; Johansson, Ellen; Moccia, Carmen; Jakubikova, Iva; Ravi, Naveen; Liang, Shawn; Carlsson, Therese; Montelius, Mikael; Patyra, Konrad; Kero, Jukka; Paulsson, Kajsa; Fagman, Henrik; et al. (Disease models & mechanisms, 2022)
Cancer cells hijack developmental growth mechanisms but whether tissue morphogenesis and architecture modify tumorigenesis is unknown. Here, we characterized a new mouse model of sporadic thyroid carcinogenesis based on inducible expression of BRAF carrying a Val600 Glu (V600E) point mutation (BRAFV600E) from the thyroglobulin promoter (TgCreERT2). Spontaneous activation of this Braf-mutant allele due to leaky activity of the Cre recombinase revealed that intrinsic properties of thyroid follicles determined BRAF-mutant cell fate. Papillary thyroid carcinomas developed multicentrically within a normal microenvironment. Each tumor originated from a single follicle that provided a confined space for growth of a distinct tumor phenotype. Lineage tracing revealed oligoclonal tumor development in infancy and early selection of BRAFV600E kinase inhibitor-resistant clones. Somatic mutations were few, non-recurrent and limited to advanced tumors. Female mice developed larger tumors than males, reproducing the gender difference of human thyroid cancer. These data indicate that BRAFV600E-induced tumorigenesis is spatiotemporally regulated depending on the maturity and heterogeneity of follicles. Moreover, thyroid tissue organization seems to determine whether a BRAF-mutant lineage becomes a cancerized lineage. The TgCreERT2;BrafCA/+ sporadic thyroid cancer mouse model provides a new tool to evaluate drug therapy at different stages of tumor evolution.
Keywords: Thyroid Neoplasms; nádory štítné žlázy; inhibitory proteinkinas; Proto-Oncogene Proteins B-raf; Point Mutation; Female; Tumor Microenvironment; Antineoplastic Agents; Mutation; protinádorové látky; myši; protoonkogenní proteiny B-raf; Mice; mutace; Thyroid Cancer, Papillary; nádorové mikroprostředí; mužské pohlaví; zvířata; ženské pohlaví; Protein Kinase Inhibitors; Animals; Male; papilární karcinom štítné žlázy; bodová mutace